Effects of an oral hydro-ethanolic purple coneflower extract on performance, clinical health and immune parameters in calves. (September 2021) - Ayrle, Hannah; Mevissen, Meike; Bruckmaier, Rupert M.; Wellnitz, Olga; Kaske, Martin; Bieber, Anna; Vögtlin, Andrea; Fricker, Raffael; Walkenhorst, Michael
Abstract: The objective of this randomized, placebo-controlled, double-blinded field trial was to investigate the effects of oral administration of purple coneflower ( Echinacea purpurea L. (EP)) on performance, health and immune parameters in calves. Calves ( n = 27) were enrolled to three groups (9 calves per group): 0.5 g EP/calf per day (ECL), 5 g EP/calf per day (ECH) or placebo. Calves were vaccinated with Bluetongue-Virus (BTV) serotype 4 vaccine to investigate EPs effects on seroconversion. Clinical and performance parameters, inter alia body weight, health and milk intake were recorded for 57 days. Blood samples were analyzed for BTV antibodies and IgG by ELISA, white and red blood cell counts by flow cytometry and mRNA abundance of various inflammatory markers in leukocytes (IL-1β, IL-8, tumor necrosis factor α (TNFα), cyclooxygenase 2 (Cox-2) and prostaglandin E synthase) was studied. The findings demonstrated no differences between groups regarding performance parameters. In all groups, calves suffered from diarrhea for a minimum of 2 days, but EP reduced the number of diarrhea days by 44% in ECL and increased the body temperature. Interestingly, ECL resulted in an increased number of respiratory disease days during the follow-up period. EP did not change blood cell and IgG counts, whereas eosinophil granulocytes were reduced in ECL. Decreased levels of hemoglobin and hematocrit were found in ECH. Prostaglandin E synthase levels in leukocytes were higher in ECL and ECH, whereas no differences were obtained for IL-1β, IL-8, TNFα and Cox-2. Due to the unexpected occurrence of BTV seropositive calves before the first vaccination, 13 calves were excluded from the evaluation on seroconversion and no statistical analyses could be performed regarding antibody production. BTV-4 antibodies were not produced in 4 placebo-calves, whereas 4 of 5 and 1 of 6 ECL- and ECH-calves produced antibodies. Further investigations are needed to draw final conclusions on mode of action and efficacy of EP in calves. Graphical abstract: Unlabelled Image Highlights: We conducted the first clinical trial with purple coneflower in the bovine species. We used two dosages of a well-defined standardized extract used for medicinal products. Besides immunomodulation, antidiarrheal effects were found. The lower dosage seemed to be more effective than the higher.